Les Pathologies Chirurgicales Néonatales À l'Hôpital National De Lamordé De Niamey: Aspects Diagnostiques, Thérapeutiques Et Pronostiques - Omid, Ali Ada Mahamoud; Hellé, Moustapha; Oumarou, Habou; Karim, Cherif Maiguizo Abdoul; Habibou, Abarchi (European Scientific Journal, ESJ, 2017)
Purpose: The purpose of this study is to describe the characteristics of the newborn and its surgical pathologies managed in the service of pediatric surgery of the National Hospital of Lamordé. Patients and Methods: It is a retrospective and descriptive study within a period of 10 years (from January 1st 2007 till December 31st 2016). The epidemiological, diagnostic, therapeutic, and evolutionary aspects were also studied. Results: The surgical pathologies of the newborn child represented 12.8 % of the hospitalized patients. The average annual incidence was 47.5 newborn children a year. The average age was of 8.71 days. The newborn children were especially old from 0 to 7 days (60,2 %) and were male (66.1 %). The most frequent pathologies were the malformations anorectales (32,2 %), the omphalocele (18.3 %), and the gastrochisis (6.5 %). The surgical operations, realized for 67.7 % patients, were especially emergencies (58.2 %). The colostomy was the most realized intervention (41.9 %). The mortality rate was 25.8 % (n=123). The post-operative mortality was 16.9 % and the nonoperative mortality was 45%. The premature mortality established 70 % of deaths (n=75). The omphalocele was the main pathology supplier of death (26 %). Conclusion: The neonatal surgical pathologies are characterized by their frequency, their diversity, the predominance of digestive system pathologies, and a high mortality. An evaluation of pronostic factors which determines the morbi-mortality is necessary.